The influence of emotional motives on the decision to use a credit card - Kasnaeny Karim; Muhammad Jibril Tajibu (Hasanuddin Economics and Business Review, 2021)
The purpose of this study was to analyze the influence of emotional motives consisting of personal factors and psychological factors on consumer decisions to use credit cards. This study involved 100 respondents, with a sampling technique based on purposive sampling. The questionnaire was distributed to respondents according to the research criteria, namely being customers of credit card users in banks in the city of Makassar, which were further analyzed using the Multiple Linear Regression model, which will test variables from emotional motives, namely personal factors, and psychological factors, on the decision to use credit cards. . The results showed that personal factors had a significant positive effect on the decision to use a credit card, while psychological factors also showed a significant positive effect on the decision to use a credit card. Thus, people in the city of Makassar use credit cards based on the encouragement of emotional motives consisting of personal factors and psychological factors.